Toward a typological profile of Lingua Franca: A view from the lexicon and word formation1. (March 2018) - Operstein, Natalie
Abstract: Although the Mediterranean contact language Lingua Franca (LF) is generally classified as a pidgin, a closer examination of the specialist literature reveals some doubts regarding this categorization. This paper approaches the classification of LF from the viewpoint of its vocabulary structure and word formation processes. The basis for the study is the lexicon of some 2000 words recorded in the anonymous didactic dictionary of 1830 that constitutes the most detailed source of information about LF. The study finds that the LF word formation processes are a detailed continuation of those of its Romance lexifiers. This finding calls for a refinement of our understanding of LF, and with it of our "typology of contact outcomes" (Winford 1997: 3). Highlights: A study of the derivational morphology of Lingua Franca. Word formation strategies of Lingua Franca continue those of its Romance lexifiers. The classification of Lingua Franca as a pidgin is questioned.